2000
DOI: 10.2337/diabetes.49.9.1543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypoglycemia on amino acid and protein metabolism in healthy humans.

Abstract: In response to hypoglycemia, healthy individuals rapidly antagonize insulin action on glucose and lipid metabolism, but the effects on protein metabolism are unclear. Because amino acids are an important substrate for gluconeogenesis and a fuel alternative to glucose for oxidation, we evaluated whether hypoglycemia antagonizes the hypoaminoacidemic and the antiproteolytic effects of insulin and changes the de novo synthesis of glutamine, a gluconeogenic amino acid. To this purpose, in 7 healthy subjects, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 66 publications
4
25
0
1
Order By: Relevance
“…This study showed that, in females, the association of type 1 DM, overweight and young age increases strikingly the insulin resistance of glucose metabolism. This conclusion is based on the comparison of the present findings with those previously reported by us using the same experimental protocol, in healthy young adult type 1 diabetic subjects [3,12,13], and in lean and obese young adults [14], and by other authors who have studied healthy and diabetic adolescents of both sexes [15].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…This study showed that, in females, the association of type 1 DM, overweight and young age increases strikingly the insulin resistance of glucose metabolism. This conclusion is based on the comparison of the present findings with those previously reported by us using the same experimental protocol, in healthy young adult type 1 diabetic subjects [3,12,13], and in lean and obese young adults [14], and by other authors who have studied healthy and diabetic adolescents of both sexes [15].…”
Section: Discussionsupporting
confidence: 57%
“…Endogenous leucine flux was calculated as previously described [12] on the basis of [ 13 C]leucine enrichment values in the last 60 minutes of the basal and the hyperinsulinemic periods.…”
Section: Analytical Determinationsmentioning
confidence: 99%
“…The glucose concentration diminished during that period of time, but it did so at a rate that was very slow compared with what we would have expected if the glucose production had been consistently reduced with the liver removal. The decrement in circulating glucose was only 15%/h, whereas we previously found that it decreased by 30-40% within 30 min during hypoglycemic clamp studies in which the glucose production was reduced by 50% and the glucose disappearance was not appreciably changed (1,4). This slow reduction in circulating glucose during the anhepatic phase might have occurred either because of a substantially maintained glucose production or because of a markedly decreased glucose uptake.…”
Section: Discussionmentioning
confidence: 78%
“…Plasma amino acid concentrations and enrichments were measured by electron impact GC-MS. Before derivatization, amino acids were isolated from plasma by use of cation-exchange columns as previously described (1). Amino acids eluted from the columns were evaporated to dryness and derivatized to form the tert-butyldimethylsilyl (TBDMS) derivative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation